Efektivitas Pentas Seni Dalam Meningkatkan Karakter Kebhinekaan Global Siswa - Riski, Sintya Triana; Ramadan, Zaka Hadikusuma (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
This study was conducted to determine the effectiveness of art performance activities on increasing the character of global diversity. The research method used is quantitative with an ex post facto approach. The research was conducted at SD Negeri 182 Pekanbaru with a sample of class VC totaling 31 students. Art performance activities are routinely carried out on Saturdays, each class that has been determined must perform various performances. The data collection instrument used was a 10-question art performance questionnaire and a 21-question global diversity questionnaire. The data analysis techniques used are validity test, reliability test, descriptive analysis, prerequisite test and test. The results showed that the data collected were normally distributed, linear and homogeneous, then the next stage of hypothesis testing was carried out through the calculation of the T test if it was known that t count> t table, namely 4.723> 1.699, it was concluded that Ha was accepted and H0 was rejected, meaning that there was an effectiveness of performing arts on increasing the character of global diversity.